(untitled) (Global Journal of Medical Research, 2018)
Ectopic pregnancy (EP) is a public health issue all over the world and remains a major gynaecological problem in contemporary gynaecological practice. We assessed the risk factors for EP among women presenting at a tertiary health facility, University College Hospital (UCH), Ibadan, Nigeria. A10 year’s retrospective study of EP cases managed in UCH. Information was collected using a proforma and data analysed using SPSS 20. A total of 337 women had ectopic pregnancy. Mean age was 29.8 +/-5.6 years and majority (82.2%) were married. Identified risk factors were previous abdominal/pelvic surgery (ies), ectopic pregnancy and abortions while common clinical features include abdominal pain, vaginal bleeding and amenorrhoea. Majority (76.6%) were ruptured while ampulla of the fallopian tube was the commonest site. EP is still a dare emergency in our environment with most women presenting after it has ruptured. However, the risk factors and presentation has not changed.